Characterizing Escherichia coli's transcriptional response to different styrene exposure modes reveals novel toxicity and tolerance insights. (26th February 2021) - Machas, Michael; Kurgan, Gavin; Abed, Omar A; Shapiro, Alyssa; Wang, Xuan; Nielsen, David
Abstract: The global transcriptional response of Escherichia coli to styrene and potential influence of exposure source was determined by performing RNA sequencing (RNA-seq) analysis on both styrene-producing and styrene-exposed cells. In both cases, styrene exposure appears to cause both cell envelope and DNA damage, to which cells respond by down-regulating key genes/pathways involved in DNA replication, protein production, and cell wall biogenesis. Among the most significantly up-regulated genes were those involved with phage shock protein response (e.g. pspABCDE/G ), general stress regulators (e.g. marA, rpoH ), and membrane-altering genes (notably, bhsA, ompR, ldtC ), whereas efflux transporters were, surprisingly, unaffected. Subsequent studies with styrene addition demonstrate how strains lacking ompR [involved in controlling outer membrane (OM) composition/osmoregulation] or any of tolQ, tolA, or tolR (involved in OM constriction) each displayed over 40% reduced growth relative to wild-type. Conversely, despite reducing basal fitness, overexpression of plsX (involved in phospholipid biosynthesis) led to 70% greater growth when styrene exposed. These collective differences point to the likely importance of OM properties in controlling native styrene tolerance. Overall, the collective behaviours suggest that, regardless of source, prolonged exposure to inhibitory styrene levels causes cells to shift from'growth mode' to 'survival mode', redistributing cellular resources to fuel native tolerance mechanisms.